Regional and occupational disparities in the wages of young blue- and white-collar workers - Uwe Blien; Van Phan (European Regional Science Association (ERSA), 2003)
According to human capital theory the wages of people, who invest a comparable amount of time and money into an education should be also comparable. Therefore, the wages of work-ers who passed a three-year occupational education in the German so-called “dual system” represent a test of the theory. The “dual system” is a specific form of education in which ap-prentices are trained in an employing firm and in school. Descriptive analyses show that average wages between different occupations only one year after finishing the education differ by about 100 percent. In the past multivariate analyses were not available. In the paper a cross-classified multilevel model with fixed effects is used to identify specific effects of occupations and regions and to control for the heterogeneity of individual workers. The data base is the IAB Employment Sample which is a one percent sample of total employment. On the basis of this data the necessary differentiation for about 100 occupations and 327 regions is possible. In Germany occupational structures in the labour market are more important than in other countries. In the paper a comparison to the structure of regional disparities is given. Several theoretical hypotheses are tested to explain the differences.
Keywords: 330